PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA SEPATU MEREK SKETCHERS) - Dwi Danesty Deccasari; Aminul amin (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2021)
Abstract, This research aims to determine the direct influence between brand image and product quality on consumer loyalty through customer satisfaction as an intervening variable. The population used in this research were all consumers who buy and wear sketchers shoes in Malang. The total samples of 70 respondents using accidental sampling. Data analysis method using path analysis (path analysis). The results of this research indicate the coefficient of determination of multiple correlation (R2) is 0.813 or 81.3%, the remaining 18.7% is influenced by other independent variables not included in this study and F count = 129.467 at a significance level of 0.000 so that it can be concluded that the variables Free consisting of brand image (X1) and product quality (X2) has a significant effect on the dependent variable of satisfaction (Y).